2019
DOI: 10.21203/rs.2.12562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood Pressure Control Practice and Determinants among Ambulatory Hypertensive Patients Attending Primary Health care facilities in Addis Ababa

Abstract: Background Hypertension is the major risk factor for cardiovascular diseases (CVDs) related morbidity and mortality. Blood pressure (BP) is often not adequately controlled in clinical practice. Information regarding BP control in primary care settings is limited in Ethiopia.The aim of this study was to assess BP control and associated factors among hypertensive patients attending primary healthcare facilities in Addis Ababa. Methods A cross sectional study was conducted in 12 health centers in Addis Ababa c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
4
10
1
Order By: Relevance
“…The other three articles were conducted in the Tigray region [ 26 , 27 , 39 ], three articles were in Addis Ababa [ 18 , 40 , 41 ], and one article was conducted in South Nations and Nationalities of People [ 17 ]. The largest sample size was 616 which was obtained from a study conducted in Addis Ababa in 2016 [ 41 ]. Of the total articles, only 9 of them [ 11 , 16 18 , 20 , 22 , 23 , 26 , 38 ] reported the overall self-care adherence of hypertensive patients ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three articles were conducted in the Tigray region [ 26 , 27 , 39 ], three articles were in Addis Ababa [ 18 , 40 , 41 ], and one article was conducted in South Nations and Nationalities of People [ 17 ]. The largest sample size was 616 which was obtained from a study conducted in Addis Ababa in 2016 [ 41 ]. Of the total articles, only 9 of them [ 11 , 16 18 , 20 , 22 , 23 , 26 , 38 ] reported the overall self-care adherence of hypertensive patients ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 9 and 8 articles were done in the Oromia region [11,22,23,27,[29][30][31][32][33] and the Amhara region [16,19,20,[34][35][36][37][38], respectively. e other three articles were conducted in the Tigray region [26,27,39], three articles were in Addis Ababa [18,40,41], and one article was conducted in South Nations and Nationalities of People [17]. e largest sample size was 616 which was obtained from a study conducted in Addis Ababa in 2016 [41].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Among the included hypertensive patients, 2534 were found to have uncontrolled BP. Eleven of the included studies used cross-sectional study design [14][15][16][17][18][19][20][21][22][23][24] while the remaining two were cohort in design [25,26]. Almost all the included studies were hospital based except for one which was conducted at health centers [18].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Similarly, health center based study in Ethiopia showed that patients who were government employee or private business were associated with less odds ratio of uncontrolled BP than housewives. 28 This might be due to increase in awareness about their problems and medications as most of government employees have higher education level as compared to house wives. Additionally, retired patients were eleven times more likely to have uncontrolled BP (AOR = 11.50, 95% CI: 1.47, 90.13, P = .02) than house wives.…”
Section: Discussionmentioning
confidence: 99%
“…Similar result was found from health center based study in Ethiopia. 28 This might be due to unaffordability of the patients to fill their medication without missing. Experience of 1 or more side effects were also associated with uncontrolled blood pressure in which patients who experienced side effects were 1.48 more likely to have their BP uncontrolled (AOR = 1.48, 95% CI: 1.22, 6.34, P = .04) than those didn’t experience side effects.…”
Section: Discussionmentioning
confidence: 99%